Varieties of capital cities : the competitiveness challenge for secondary capitals - Kaufmann, David, 1985-; Edward Elgar Publishing (Edward Elgar Pub., Inc., 2018)
The political and symbolic centrality of capital cities has been challenged by increasing economic globalization. This is especially true of secondary capital cities; capital cities which, while being the seat of national political power, are not the primary economic city of their nation state. David Kaufmann examines the unique challenges that these cities face entering globalized, inter-urban competition while not possessing a competitive political economy. Varieties of Capital Cities offers empirically rich case studies of four secondary capital cities: Bern, Ottawa, The Hague, and Washington, DC. Analysed with an innovative research framework, this book shows through its clearly structured analysis, that while the pressures facing these cities are the same, the mechanisms they employ to cope with them are very different. They have formulated a wide variety of policies to supplement their capital function with economically promising profiles, even though they cannot escape their destinies as government cities. This book is an impressive contribution to an area of study largely neglected by urban studies, political science, and economic geography. With vital lessons for urban policy makers, the interested practitioner will find a pool of inspiration for their urban strategies. Students and scholars of these subjects will find this book interesting, and will also find it invaluable as a lesson for how to develop and execute comparative case studies.
Contents: Preface and acknowledgements -- 1. Introduction: the competitiveness challenge for secondary capital cities -- 2. How to study locational policies in secondary capital cities: an interdisciplinary analytical framework -- 3. The cases under scrutiny -- 4. Bern: the government city -- 5. Ottawa: the fragmented city -- 6. The Hague: the international government city -- 7. Washington, D.C.: the capital of the free world -- 8. Comparing locational policies in secondary capital cities -- 9. Conclusion: understanding the variety of locational policies in secondary capital cities -- Appendix: Data and Methodology -- Bibliography -- Index.
Includes index.
Includes bibliographical references.
Keywords: Capitals (Cities) -- Economic aspects; Capitals (Cities) -- Political aspects; Electronic books